The Effects of Agency Problems and Dividend Policy on the Asymmetric Behaviour of Selling, General and Administrative Expenses: Does Ownership Structure Matter? - Okechukwu Enyeribe Njoku,; Younghwan Lee,; Jeong-Ho Koo, (Asian Academy of Management Journal of Accounting and Finance, 2024)
This article investigates the effects of agency problems and dividend policy on the asymmetric behaviour of Selling, General, and Administrative (SG&A) expenses, with an emphasis on Korean business ownership structures. Employing a robust dataset of 4,279 observations from the Korean Composite Stock Price Index from 2011 to 2021, our empirical investigation combined multiple regression models such as OLS, fixed effects, random effects and the Generalised Method of Moments (GMM) to contain endogeneity problems. The research objectives include the examination of the relationship between SG&A cost asymmetry and agency problems, the impact of dividend policy on SG&A costs, and the intervening function of Korean business ownership structures, particularly Chaebols. Unexpectedly, the results reveal that higher free cash flow is linked to lower SG&A cost asymmetry, suggesting that agency concerns can be mitigated in such corporations. Improved asset utilisation increases cost asymmetry, whereas larger operating expenses reduce asymmetry. Furthermore, higher cash dividends and payout ratios are associated with reduced SG&A cost asymmetry, which contradicts the premise that dividend constraints correlate with a higher degree of cost asymmetry. According to ownership structure analysis, Chaebols' concentrated ownership results in stronger control over cash flow, eliminating cost asymmetry more efficiently than in non-Chaebol firms. These findings add to the literature on agency theory, cost behaviour, and corporate governance, providing managers and shareholders with beneficial insights. To promote business sustainability, improved handling of agency concerns and cost efficiency, this study recommends tailored corporate governance policies that takes ownership structures into account.